Pulmonary Hyalinizing Granuloma Mimicking Primary Lung Cancer: An Unusual Case Involving a Pulmonary Tumor - Hideki Marushima; Hiroki Sakai; Reimi Yoneyama; Hiroyuki Kimura; Tomoyuki Miyazawa; Motohiro Chosokabe; Masahiro Hoshikawa; Koji Kojima; Masayuki Takagi; Hisashi Saji (Case Reports in Pulmonology)
Pulmonary hyalinizing granuloma is a very rare benign condition. This study describes a case involving pulmonary hyalinizing granuloma in a 76-year-old man who presented with a solitary pulmonary nodule, determined through chest radiography and computed tomography, that mimicked primary lung cancer. To establish a definitive diagnosis, tumor resection was performed with histopathological analysis indicating pulmonary hyalinizing granuloma. Radiographic findings in previously reported cases showed that most patients had well-defined margins and usually bilateral, multiple lesions. In our case; however, the solitary ill-defined tumor mimicking lung cancer is an uncommon location for this rare condition.